The Role of Spiritual Leadership in Internalizing Environmental Values in Islamic Eco-Madrasah - La Hadisi; Jumarddin La Fua; Dirman Dirman; Muhammad Shaleh Assingkily; Harson Harson; Nur Khofifa Ayu Harisatyma (Nazhruna: Jurnal Pendidikan Islam, 2025)
Abstract Environmental education programs in faith-based schools have predominantly focused on measurable outcomes and behavioral impacts, overlooking the critical role of leadership in cultivating sustainable environmental culture. This study examines how spiritual leadership influences the internalization of environmental values within Islamic educational institutions. Using a qualitative multiple-case study approach, this research investigates the mechanisms of integration of environmental ethics across seven eco-certified madrasahs in Southeast Sulawesi, Indonesia. Data were collected through in-depth interviews with forty-two informants comprising school leaders, teachers, and students, complemented by document analysis and participatory observation. The study draws on Lickona’s character education theory to examine the moral and spiritual dimensions of environmental leadership. Three critical mechanisms emerged. First, spiritual leaders catalyze voluntary environmental stewardship by modeling eco-conscious behaviors rooted in Islamic teachings, creating authentic commitment rather than compliance. Second, systematic cultivation of environmental care culture transforms isolated activities into sustained institutional practices through ritualized habits and shared values. Third, curricular integration strengthens ecological consciousness by embedding faith-based environmental ethics across subject areas. This study demonstrates how spiritual leadership frameworks effectively advance environmental education beyond instrumental approaches. The findings offer practical implications for reconceptualizing environmental programs as integral character formation in school curricula and certification frameworks, developing professional development programs cultivating spiritual-ecological leadership competencies, and designing implementation models prioritizing cultural embedding through ritualized practices, offering transferable insights for sustainable education policy in diverse cultural contexts.